Pandemic supply chain research: A structured literature review and bibliometric network analysis - David Swanson; Luis Santamaria (Logistics, 2021)
In early 2020, COVID-19 infected people throughout the world and brought world commerce to a standstill. Many believe that governments and global businesses were not as prepared as they should have been. While academics have occasionally predicted the economic problems that could result from pandemics, until 2020, there had been scant research that addresses supply chain management issues during pandemics. Eighty-four percent of all pandemic supply chain research was published in the first ten months of 2020. Since the world now finds itself operating supply chains in response to the pandemic, this literature needs to be summarized and articulated for understanding and future research. This literature review addresses that need by summarizing the research which has been generated since 1997, focusing primarily on the bulk of the research that has been published since the COVID-19 pandemic began. Research tools are used to summarize the literature citations, and the articles are coded according to some important variables to further delineate their details. This research also includes a bibliometric co-citation analysis, which clusters the pandemic supply chain literature by author, journal, and article. The findings are that pre-COVID-19 research on pandemic supply chains was primarily about influenza and the healthcare supply chain, whereas post-COVID-19 research provides more analysis of the food supply chain and uses a wider variety of research methods, including simulation, modeling, and empirical methods.
Keywords: 650; coronavirus; COVID-19; epidemic; influenza; literature review; pandemic; supply chain